PENERAPAN MODEL STUDENT TEAMS-ACHIEVEMENT DIVISIONS TIPE SHARED UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF DAN SIKAP ILMIAH SISWA PADA MATERI POKOK CAHAYA - Fiandi, Chandra Okta (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2015)
Abstract This study aims to analyze the improvement of cognitif ability and scientific attitudes of students through the application of learning models Student Teams-Achievement Divisions (STAD) on a shared type of integrated science teaching in the subject matter light. The research method used was Quasi Experiment with the design of The mathing-Only pretest-posttest control group. This research was conducted in 2014/2015 academic year Class VIII SMP Negeri 01 Mapat Tunggul Pasaman of West Sumatra province. Data collected through pretest and posttest cognitive abilities in the form of a written multiple choice questions, as well as observation sheets scientific attitude of student. The mean N-Gain increase students' cognitive abilities with the application of STAD middle category and an increase in classes that use conventional learning models in the category of tranquility. Furthermore, the data were analyzed by using Independent Sample t-Test. The result obtained there is a significant increase in class which uses the learning model STAD in enhancing students' cognitive abilities. On a scientific attitude of students, obtained an increase but not significant between experimental class and control class in the application of integrated science teaching shared type in the subject matter light.Â AbstrakPenelitian ini bertujuan untuk menganalisis peningkatan kemampuan kognitif serta sikap ilmiah siswa melalui penerapan model pembelajaran Student Teams-Achievement Divisions (STAD) pada pembelajaran IPA terpadu tipe shared pada materi pokok cahaya. Metode Penelitian yang digunakan adalah Quasi Experiment dengan desain The Mathing-Only Pretest-Posttest Control Group. Penelitian ini dilaksanakan di Kelas VIII tahun pelajaran 2014/2015 SMP Negeri 01 Mapat Tunggul Kabupaten Pasaman Provinsi Sumatera Barat. Pengumpulan data dilakukan melalui pretest dan posttest kemampuan kognitif berupa soal tertulis pilihan ganda, serta lembar obesrvasi sikap ilmiah siswa. Rerata N-Gain peningkatan kemampuan kognitif siswa dengan penerapan model STAD berada pada kategori sedang dan peningkatan pada kelas yang menggunakan model pembelajaran konvensional pada kategori redah. Selanjutnya data dianalisis dengan menggunakan Independent Sample t-Test. Hasilnya menunjukkan terdapat peningkatan yang signifikan pada kelas yang menggunakan model pembelajaran STAD dalam meningkatkan kemampuan kognitif siswa. Pada aspek sikap ilmiah siswa, peningkatan diperoleh pada kelas eksperimen, namun tidak signifikan, pada penerapan pembelajaran IPA terpadu tipe shared pada materi pokok cahaya. KataPermalink/DOI: http://dx.doi.org/10.15408/es.v7i2.1810